Product-Type Operators on the Space of Fractional Cauchy Transforms. (9th March 2022) - Fan, Zeng; Guo, Xin
Abstract : The space of fractional Cauchy transforms plays a central role in classical complex analysis, harmonic analysis, and geometric measure theory. In this paper, we study the boundedness and compactness of product-type operators from the space of fractional Cauchy transforms to the Zygmund-type space in terms of the function theoretic characterization of Julia–Carathéodory type.